Methane production in the oxygenated water column of a perennially ice‐covered Antarctic lake - Wei Li; John E. Dore; August J. Steigmeyer; Yong‐Joon Cho; Ok‐Sun Kim; Yongqin Liu; Rachael M. Morgan‐Kiss; Mark L. Skidmore; John C. Priscu (Limnology and Oceanography, 2020)
Aerobic methane production in aquatic ecosystems impacts the global atmospheric budget of methane, but the extent, mechanism, and taxa responsible for producing this greenhouse gas are not fully understood. Lake Bonney (LB), a perennially ice‐covered Antarctic lake, has cold hypersaline waters underlying an oxygenated freshwater layer. We present temporal methane concentration profiles in LB indicating methane production in the oxygenated (> 200% air saturation) water. Experiments amended with methylphosphonate (MPn) yielded methane generation, suggesting in situ methanogenesis via the carbon‐phosphorus (C‐P) lyase pathway. Enrichment cultures from the lake were used to isolate five bacterial strains capable of generating methane when supplied with MPn as the sole P source. Based on 16S rRNA gene sequencing, the isolates belong to the Proteobacteria (closely related to Marinomonas , Hoeflea , and Marinobacter genera) and Bacteroidetes ( Algoriphagus genus). 16S rRNA metagenomic sequencing confirms the presence of these taxa in LB. None of the isolated species were reported to be capable to produce methane. In addition, orthologs of the phosphoenolpyruvate mutase gene ( PepM ) and methylphosphonate synthase ( MPnS ), enzymes involved in phosphonate and MPn biosynthesis, were widely spread in the LB shotgun metagenomic libraries; genes related to C‐P lyase pathways ( phn gene clusters) were also abundant. 16S rRNA and mcrA genes of anaerobic methanogens were absent in both 16S rRNA and metagenomics libraries. These data reveal that in situ aerobic biological methane production is likely a significant source of methane in LB.